PERAN MASJID ‘AINUL YAQIN’ UNIVERTAS ISLAM MALANG DALAM PENDIDIKAN ISLAM - Diyah Mukti Pratiwi (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Thiss studyc aimsb tov describeb Islamicd educationq activitiesq carriedq outq atq Ainulq Yaqin Mosque, Malanga Islamica University. Ina addition, thea studya alsoa aimsa toq determineq the factors ofq theq successq ofq Islamicq educationq inq theq Ainulq Yaqinq Mosque, Malangq Islamicq University. Thisq researchq isq a typeq ofq qualitativeq research. Theq approachq used is descriptiveq study. The researchq subjectsq wereq theq takmirq ofq theq Ainulq Yaqinq Mosqueq in theq Islamicq Universityq ofq Malang, theq youthq ofq theq Islamicq Universityq of Malang, theq Islamicq boardingq schoolq studentsq at the Ainulq Yaqinq Campus, Islamicq Universityq ofq Malang. Dataq collectionq wasq carriedq outq usingq theq methodq of documentationq andq interviews. Whileq theq methodq of qdataq analysisq usesq inductiveq methodsq withq analyticalq descriptiveq decompositionq models. Theq resultsq showedq that the Ainulq Yaqinq Mosqueq in Malangq Islamicq Universityq hadq a roleq asq anq effectiveq Islamicq educationq institution. qThis qcan qbe qseen qfrom qthe qmany qresults qof Islamic education qthat qhave qbeen qachieved qincluding qpracticed qin qthis qyear's qRamadan, takmirq Ainulq Yaqinq Mosqueq heldq a programq calledq Gebyarq RamadhanqqKreatif in which thereq areq manyq activitiesq carriedq outq by qTeen Mosquesq (Remas) qfrom qUnisma studentsq as qfollows : Kitabq Kuning Studyq afterq FajrqqPrayer, Mutiaraq Wisdomq after the Dhuhur Prayer, The Book of Muktatofat every day at 1:00 p.m. untilq Asar,q Takjil qis free with pilgrims, qwhere qtakmir qprovides q200-300 takjil every qday, supervisedq Prayersq in congregation, Ceramahq Tawaus Al -Qur'an, Providing qcompensation to duafa and orphans, Collection qof qzakat qfitrah qand malls, qEid qprayer. Pillars qof qFaith qand qPillars of Islam well. In addition, the qcongregation qis qalways a qprayer qThe qfactors that support the qsuccess of Islamic education at the qAinul qYaqin qMosque in Malang qIslamic qUniversity qinclude exemplary factors, method qfactors and the solidarity factor of the ta'mir and adolescent mosques as qwell qas qthe qIslamic qboarding qschool qstudents qof the qAinul qYaqin Unisma Campus